Preparation and Study of Solid Dispersions of Acyclovir with Starch and Carboxymethylcellulose - Kryuk, T. V.; Popyrina, T. N.; Romanenko, N. A.; Ivanov, P. L.; Svishcheva, N. B.; Akopova, T. A.; Khavpachev, M. A. (Polymer science. Series C, 2024)
Solid dispersions based on acyclovir and polysaccharides (starch and sodium carboxymethylcellulose) have been prepared by means of mechanochemistry. Mechanical co-processing of the drug and the polymers in a ball mill, an extruder, and a pulse mechanical action cell has led to amorphization of acyclovir, followed by its uniform distribution in the polymer matrix. A set of the IR and UV spectroscopy, DSC, and X-ray diffraction analysis data has revealed the presence of intermolecular interactions between the polysaccharide matrix and the drug. The obtained materials can be considered as potential system for further investigation as solid formulations of acyclovir with improved bioavailability.